DAMPAK KERJASAMA ACFTA TERHADAP EKSPOR KARET INDONESIA - CHINA (2010-2011) - Wita, Silvia; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The purpose of this research is to discuss about the imppact of ACFTA cooperation toIndonesian rubber exports to China. This research will cofus on analysing the ASEAN-Chinafree trade agreement and their effect on the economy of Indonesian especially Indonsiandomestic industry. This research was analysed by using integration theory. Background ofthis economic integration theory was explained by Bela Balasa. The results of this research isto find out the impact of ACFTA cooperation exports rubber to China in 2010-2011.Wherethere has been a decline in Indonesian rubber exports to China. Additionally to find outaction of indonesian government to protecting Indonesian rubber industry. It’s doing with putoutside many wisdom on ACFTA cooperation to increased economic Indonesian.Keywords: ACFTA, rubber, Indonesia, China